A prospective study of anal cancer screening in HIV-positive and negative MSM. (1st June 2016) - Schofield, Alice M.; Sadler, Laura; Nelson, Linsey; Gittins, Matthew; Desai, Mina; Sargent, Alex; McMahon, Raymond F.T.; Hill, James; Crosbie, Emma J.; Patnick, Julietta; Kitchener, Henry C.
Abstract : Objective: The study sought to establish the feasibility and acceptability of anal screening among men MSM. Design: Prospective cohort study. Setting: Sexual health clinics in tertiary care. Patients: Known HIV-positive and negative MSM who have anoreceptive intercourse. Intervention: Anal screening with human papilloma virus (HPV) testing, liquid-based cytology and high-resolution anoscopy with biopsy of anoscopic abnormalities. Participants completed questionnaires at baseline and at 6 months. Results: Anal HPV was highly prevalent in MSM (HIV-positive, 88% and HIV-negative, 78%). Despite the high prevalence of cytological abnormality in both HIV-positive (46.2%) and negative (35.0%) MSM, almost half of anal intraepithelial neoplasia (AIN) of all grades were associated with negative cytology. Anoscopically directed biopsies detected AIN3 or worse (AIN3+) in 14 of 203 (6.9%) of HIV-positive MSM and three of 81 (3.7%) HIV-negative MSM. The corresponding prevalence of AIN2+ was 26.6 and 20.9%, respectively. One case of AIN3 was detected at the second visit. Screening was considered to be highly acceptable by participants. Conclusion: The high prevalence of high-risk-HPV and frequency of false negative cytology in this study suggest that high-resolution anoscopy would have most clinical utility, as a primary screening tool for anal cancer in a high-risk group. The prevalence of AIN3+ in HIV-positive MSM lends support for a policy of screening this group, but the high prevalence of lower grade lesions which do not warrant immediate treatment and the limitations of treating high-grade lesions requires careful consideration in terms of a screening policy.